In the Spiritual and Moral Heritage of the Uzbek People Ideas of Military Patriotism and its Interpretation - Z. A. Abduazimova; A. Usmanov (Researchparks Publishing, 2022)
The article talks about the moral and moral heritage of the Uzbek people, the observance of the moral rules of military servicemen, the ideas of military patriotism and its interpretation, the military serviceman's love for the Motherland and loyalty to the military oath.